2008
DOI: 10.1007/s12197-008-9059-x
|View full text |Cite
|
Sign up to set email alerts
|

US elections and monthly stock market returns

Abstract: Market Returns, Election, Democratic, Republican, G10, G18,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 7 publications
0
28
0
1
Order By: Relevance
“…A time series analysis of fiscal expenditure of Malaysia is done from 1967 to 1997 to show how systematically ruling party create favors for its supporters in non-democratic regime. Jones and Banning (2009) observed no such significant difference in monthly stock returns. They also suggested that it is not appropriate to invest using a rule of thumb because investing decision is not as simple as just based on which political party the president belongs to.…”
Section: Brief Literature Reviewmentioning
confidence: 83%
“…A time series analysis of fiscal expenditure of Malaysia is done from 1967 to 1997 to show how systematically ruling party create favors for its supporters in non-democratic regime. Jones and Banning (2009) observed no such significant difference in monthly stock returns. They also suggested that it is not appropriate to invest using a rule of thumb because investing decision is not as simple as just based on which political party the president belongs to.…”
Section: Brief Literature Reviewmentioning
confidence: 83%
“…Santa-Clara and Valkanov (2003) find the excess stock market returns to have been higher under Democratic than Republican presidencies, with a value-weighted portfolio 9% higher and with an equal-weighted portfolio 16% higher. However, Jones and Banning (2009) investigate possible relations between stock market performance and various occurrences in US elections using monthly market returns over a period of 104 years. They find little evidence that market returns vary based on partisan control of the government.…”
Section: Markets Returns and Politicsmentioning
confidence: 99%
“…Jones and Banning (2009) investigate various combinations of the White House, the US Congress, or both.…”
mentioning
confidence: 99%
“…A significant number of past studies deal with the impacts of political uncertainty on financial market performances (see, inter alia, He, Lin, Wu, & Dufrene, ; Jones & Banning, ; Li & Born, ; Nippani & Medlin, ; Pantzalis et al, ; Sy & Al Zaman, , etc.). Most of these researches provide deep evidence revealing that political uncertainty significantly influences risk and return in financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, positive price changes should be anticipated after the election, that is, until uncertainty about the policies to be achieved by the winner is resolved. A significant number of past studies deal with the impacts of political uncertainty on financial market performances (see, inter alia, He, Lin, Wu, & Dufrene, 2009;Jones & Banning, 2009;Li & Born, 2006;Nippani & Medlin, 2002;Pantzalis et al, 2000;Sy & Al Zaman, 2011, etc.). Most of these researches provide deep evidence revealing that political uncertainty significantly influences risk and return in financial markets.…”
mentioning
confidence: 99%